Coordination in integrated area development program : a case study of Nusa Tenggara Agriculture Support Project (NTASP), Lombok Timur district, Nusa Tenggara Barat province, Indonesia - Bakar, Sjofjan; Demaine, Harvey; Routray, Jayant Kumar; Kammeier, Hans Detlef; Government of Indonesia Ministry of Home Affairs (Bangkok : Asian Institute of Technology, 1989)
This study deals with coordination in Integrated Area Development in the Nusa Tenggara Agriculture Support Project (NTASP). Coordination in this project is required among many agencies at National, Province and District level . Although NTASP has been conducted since 1985, there are many problems found in coordination, since the tendency of sectoral orientation among the agencies is still quite strong. Poor coordination, in both the vertical and horizontal dimensions, insufficient adaptation of national policies to provincial and districts conditions as well as frequent the failure of officials to realize that coordination is the key element in bringing about project success are responsible for these problems. In this study four factors influencing coordination were examined ;project organization , communication, skill & number of personnel and clarity of job description. These factors were examined in turn in relation t o the various stages of the planning project cycle of NTASP, planning, project approval , implementation, financial regulation, monitoring/reporting and evaluation. According to the analysis , coordination is weak in financial regulations, and in monitoring/evaluation but is reasonably strong in project planning and approval. Coordination with regard to project implementation is not so good because this is influenced by financial regulations . In order to over come the problem of coordination, it is time to Ministry of Home Affairs to assess coordination of all projects in Integrated Area Development program in other provinces in Indonesia. The other suggestions are that there should be one guideline of IADP and also to reduce project organizations that are not so important , as well as decentralize financial regulation at provincial level.
A Thesis Submitted in Partial Fulfillment of the Requirements for the Award of the Degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1989
Keywords: Agricultural administration -- Indonesia